Interosseus Wiring of Distal Radius Fractures With Volar Comminution. Issue 1 (March 2019) - Githens, Thomas; Murphree, Jacob; Daneshfar, Cy; MacKay, Brendan
Abstract : Interosseous wiring is a technique that has been used for decades to help achieve interfragmentary compression and subsequent osteosynthesis in a number of fracture patterns. Comminuted distal radius fractures with larger volar fragments present challenges for reconstruction and reestablishment of length, rotation, and alignment of the metadiaphyseal region. In many instances, the use of bridge plating in these fracture patterns is difficult as the fragments are prone to displacement. Utilizing interosseous wiring in distal radius fractures with larger volar fragments provides an extraordinarily useful technique, allowing for anatomic reduction and restoration of the articular block. This stabilizing aid provides an ideal reduction for proper placement of a volar locked plate. This study describes the technique of interosseous wiring in a 75-year-old female patient with distal radius and ulnar fractures with subsequent volar locked plate placement. This technique provides an efficient and cost-effective tool to improve anatomic reduction, interfragmentary compression, and proper plate placement in distal radius fractures of this morphology.